Characteristics of Lithofacies Combinations and Reservoir Property of Carbonate-Rich Shale in Dongying Depression, Eastern China - Liu, Huimin; Zhang, Shun; Liu, Yali; Zhang, Pengfei; Wei, Xiaoliang; Wang, Yong; Zhu, Deyan; Hu, Qinhong; Yang, Wanqin; Tang, Dong; Ning, Fangxing; Guan, Li; et al. (Frontiers in Earth Science, 2022)
Shale oil wells are often drilled in multiple lithofacies combinations, rather than a single lithofacies. In view of the exploration and production practice, it is necessary to classify the shale lithofacies combinations. The basic characteristics of carbonate mineral-rich shales in the upper part of the fourth Member of the Shahejie formation (Es4s) were analyzed by mineral analysis, organic geochemical and reservoir property experiment. The depositional setting was determined using geochemical elements and mineral composition, and the lithofacies combinations of the shale were divided based on the depositional setting and vertical changes in lithofacies association. Lithofacies combinations include (1) laminated argillaceous limestone interbeds with the calcareous mudstone (LLM); (2) Laminated argillaceous limestone interbedded with dolomite (LLD); (3) Calcareous mudstone intercalated with argillaceous limestone (BML). LLM formed in a semi-humid, with limited detrital provenance, while LLD was mainly the product of an arid climate, little detrital input, semi-deep water, and a strongly reducing saltwater environment. In addition to the basal strata in the center of the depression, The LLD lithofacies combination was also widely developed on the gentle slope and the slope area transitional to deep depression in the south of the basin. BML was mainly formed in semi-humid climate, brackish, deep water, and a reducing environment with many detrital provenances. The porosity in LLM and LLD consists of various types. Intercrystalline pores in clay minerals, intercrystalline pores and dissolution pores in carbonate minerals, interbedded fractures and abnormal high pressure fractures are well developed. The pore size distribution range of both LLM and LLD is large. Porosity of LLM is slightly higher than that of LLD. Interlayers with higher dolomite content have higher permeability. The types of pores in BML with no significant laminae characteristics are less abundant, and it is difficult to form an effective reservoir porosity network from the pores and microfractures, and hence the reservoir physical properties are relatively poor. Oil saturation index indicates that both LLD and LLM of medium-low degree of evolution have good oil content.